2015
DOI: 10.3989/gya.1299142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different roasting conditions on the nutritional value and oxidative stability of high-oleic and yellow-seeded <em>Brassica napus</em> oils

Abstract: SUMMARY:This study was conducted to evaluate the possibility of enhancing the nutritional value and oxidative stability of rapeseed oil obtained from seeds subjected to thermal treatment prior to pressing. The yellowseeded and high-oleic B. napus lines, harvested in Poland, were roasted prior to pressing for 1 h at 100 and 150 °C. This study highlighted how rapeseed breeding lines affect the quality profile of the oils obtained both before and after the roasting process. In principle, the high-oleic B. napus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The maximum values (0.28-0.3) were recorded for the temperature of 175°C. This result is consistent with previous works on pine nuts, colza, and sesame oils [ 16 18 ]. The increase in acidity could be explained by the release of FA following the hydrolysis of the triglycerides which constitute the major components of vegetable oils.…”
Section: Resultssupporting
confidence: 94%
“…The maximum values (0.28-0.3) were recorded for the temperature of 175°C. This result is consistent with previous works on pine nuts, colza, and sesame oils [ 16 18 ]. The increase in acidity could be explained by the release of FA following the hydrolysis of the triglycerides which constitute the major components of vegetable oils.…”
Section: Resultssupporting
confidence: 94%
“…Thus, the seeds thermal pretreatment under the harshest conditions (10 min of microwave radiation, roasting for 100 min at 165°C) increased IP twofold, when compared to the control oils. Favorable effect of rapeseed thermal pre-treatment on the oxidative stability of oil was confirmed both in a studies investigating the effect of microwaving [6,8,10] and roasting [24]. These studies emphasized a significant effect of the canolol (4-vinylphenol), formed under elevated temperatures, in addition to improved extractability of compounds possessing antioxidative properties, such as tocopherols and carotenoids as a major factors responsible for an enhancement of the oxidative stability of the oils pressed from thermally pre-treated rapeseeds.…”
Section: Oxidative Stability Parameters Oil Oilsmentioning
confidence: 79%
“…Anjum et al found p ‐AnV to be the most sensitive of the parameters describing oxidative state of oil to changes in the chemical properties of oils pressed from microwave treated sunflower seeds (5–10 min, 500 W). Rękas et al reported a gradual increase of p ‐AnV with higher roasting temperature of rapeseed (100 and 150°C). Cai et al found that the increase of roasting time (10–60 min at 150°C) resulted in the higher accumulation of p ‐AnV in pine nut oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[36,37] The composition of fatty acids can [31] Rapeseed oil is characterized by lower Cox value than linseed (12.62-13.97), camelina (8.76-9.94), or poppy seed oil (6.31, 9.54) which translates into its higher oxidative stability. The fatty acid composition of analyzed oils was comparable to the results available in the literature.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%